A Systematic and Simple Scoring System for Histological Analysis of the Mouse Intervertebral Disc during Natural Ageing, Degeneration, and Regeneration. (May 2014) - Wing Chan, W. Cheuk; Tam, V.; Cheah, K. SE; Cheung, K. MC; Chan, D.
Introduction: Intervertebral disc (IVD) degeneration is a condition associated with the decline of water, proteoglycans and cells from the IVD, and is associated with low back pain. The etiology of IVD degeneration has both genetic and environmental components, however, the mechanisms of the alterations associated with degeneration are not fully understood. In addition, to changes in the biochemistry, hydration, and cell number in the IVD, different types of cells are observed in health and during degeneration. To study the process of IVD degeneration, this requires the use of good in vivo animal models. Several animal models are currently used to study disc degeneration, although various species have their own advantages and disadvantages in relation so size and similarity to the human phenotype. The mouse while does exhibit differences to the human phenotype, is still a particularly useful tool for studying degeneration. The major advantage of the mouse is the ability to make transgenic mice, which can elucidate specific gene functions during IVD degeneration. Moreover, established mouse degeneration models indicate that after induction of degeneration which results in gradual degenerative changes to the disc, the cellular phenotype changes from a notochordal-like phenotype, to that of a chondrocyte-like cell. However, one of the drawbacks for using the mouse is a lack of a systematic and uniform method for assessing levels of degeneration of the mouse IVD. The use of the mouse model in several studies has also resulted in the use of many different methods and criteria to histologically assess disc degeneration, which sometimes do not include sufficient details on the characteristics that were assessed. Moreover, the use of a particular stain in two different laboratories may not result in the same staining pattern observed due to user variation. The creation of a systematic scoring system for mouse IVD degeneration that is applicable to different mouse models of degeneration would be particularly advantageous as this would allow for cross study comparisons of IVD degeneration. Materials and Methods: In this study, we induced degeneration in the mouse via annular puncture (injury model) in addition to the tail loop method (compression model) and studied the histology of the mouse IVD in health, and during degeneration. We analyzed the discs of commonly used mouse strains, at differing stages of degeneration, and of differing ages to examine the morphological features. We were able to identify key common features in the different IVD compartments that were consistently observed in the healthy state, the early stages of degeneration, as well as the late stages of degeneration. These features were categorised into a scoring system that was focused on changes in the nucleus pulposus (NP), annulus fibrosus (AF), and the NP/AF border which culminated with a combined score to indicate the level of degeneration. Results: The scoring system was subsequently tested on subjects, some of which were familiar or not familiar with the histology of the mouse IVD. It was found that overall, the scoring system containing the defined criteria was user-friendly, even for inexperienced users analyzing the mouse disc, and resulted in relatively low levels of variation between different users. Conclusion: The criteria that were defined in this study are applicable to differing mouse strains and from the postnatal stage to the aged mouse. This scoring system may be a useful tool for analyzing IVD degeneration, as well as regeneration, and can accommodate for cross study comparison. Disclosure of Interest None declared